2016
DOI: 10.1088/0031-9155/61/5/2025
|View full text |Cite
|
Sign up to set email alerts
|

Time resolution of the plastic scintillator strips with matrix photomultiplier readout for J-PET tomograph

Abstract: Abstract. Recent tests of a single module of the Jagiellonian Positron Emission Tomography system (J-PET) consisting of 30 cm long plastic scintillator strips have proven its applicability for the detection of annihilation quanta (0.511 MeV) with a coincidence resolving time (CRT) of 0.266 ns. The achieved resolution is almost by a factor of two better with respect to the current TOF-PET detectors and it can still be improved since, as it is shown in this article, the intrinsic limit of time resolution for the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(120 citation statements)
references
References 34 publications
1
116
0
Order By: Relevance
“…In present day Positron Emission Tomography (PET) imaging systems, suspected false coincidence events are removed using energy discrimination and correction techniques. With the advent of Compton camera technology [1][2][3][4][5], it has been suggested that entanglement of the annihilation photons can be used as an additional discriminator to increase the accuracy of eliminating false coincidence events, thereby improving image quality [6]. However, before entanglement can be used, fundamental issues relating to kinematic outcomes of Compton scattering of annihilation photons must be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…In present day Positron Emission Tomography (PET) imaging systems, suspected false coincidence events are removed using energy discrimination and correction techniques. With the advent of Compton camera technology [1][2][3][4][5], it has been suggested that entanglement of the annihilation photons can be used as an additional discriminator to increase the accuracy of eliminating false coincidence events, thereby improving image quality [6]. However, before entanglement can be used, fundamental issues relating to kinematic outcomes of Compton scattering of annihilation photons must be resolved.…”
Section: Introductionmentioning
confidence: 99%
“…However, resolution of the Z coordinate (along the scintillator strips) and of photon recording time in J-PET are correlated and dependent on the signal reconstruction method used due to the specific features of this detector [16,[24][25][26]. Moreover, they are subject to a possible future improvement with an advancement of reconstruction methods applied in J-PET based on multi-SiPM readout [27]. Therefore, reconstruction studies were performed both for fixed detector resolutions of σ(t hit )=80 ps and σ(z hit )=0.93 cm presently achieved with prototypes [15] and for these resolutions varying in the range from 0 ps to 160 ps and from 0 cm to 2 cm, respectively.…”
Section: Principle Of the O-ps→ 3γ Decay Reconstructionmentioning
confidence: 99%
“…3Simulated spectra of deposited energy in plastic scintillators for gamma quanta from annihilation and for de-excitation gamma quanta originating from isotopes indicated in the legend. The spectra were simulated including the energy resolution of the J-PET detector [20] and were normalized to the same number of events
Fig. 4Scheme of sodium decay and formation of ortho-positronium
…”
Section: Performance Assessment: Monte Carlo Simulationsmentioning
confidence: 99%
“…The spectra were simulated including the energy resolution of the J-PET detector [20] and were normalized to the same number of events…”
Section: Performance Assessment: Monte Carlo Simulationsmentioning
confidence: 99%
See 1 more Smart Citation